O uso de membrana de látex natural como membrana oclusiva associada ao laser de baixa intensidade em regeneração óssea - Queiroz, Aline Maria Papani de (2008)
The bone structure is a live tissue, which serves as structural support for the organism and reservoir of several organic and inorganic molecules, with great renewal capacity. The bone tissue is metabolically active, and is able to repair itself when suffering damages, but the bone injuries involve damages to the health, as well as problems of socio-economic order. If the repair period of the damage is extended, the consequences will be proportionately bigger. So, the concern is shortening the period of bone consolidation becomes important. The search and development of techniques and materials seek to abbreviate the regenerative period of the bone damage has been focus of much research. Materials as membranes and techniques such laser irradiation are part of the focus of this research. The latex is a biocompatible material with high mechanical strength and that can accelerate the angiogenesis. It presents as other advantages, elasticity, capacity to induce neoformation tissues and the low cost of the material. The laser is an electromagnetic wave constituted by a beam of photons of same frequency, with a wavelength phase which acts to balance and to normalize the functional activity of the cell, also has analgesics, anti-inflammatory and anti-edematous effects. The aimed of this study was to evaluate the response of the membrane use of natural latex derived from the Hevea brasiliensis as occlusive membrane, associated with the low-intensity laser irradiation (Arseniete Galium) in the rat s calvaria bone regeneration. The latex membranes were implanted in rat s calvaria on surgical bone defects. The bone neoformation was analyzed by histological studies and histomorphometric analyses. The results showed that the group D: MB + L (membrane + laser) presented the most advanced process of bone regeneration, followed by other groups, being that in the regenerative process in the control group showed themselves more incipient in relation to the experimental groups.